Swelling ability and behaviour of bentonite-based materials for deep repository engineered barrier systems: Influence of physical, chemical and thermal factors - Mohammed Alzamel; Mamadou Fall; Sada Haruna (Journal of Rock Mechanics and Geotechnical Engineering, 2022)
Compacted bentonite–sand (B/S) mixtures have been used as a barrier material in engineered barrier systems (EBSs) of deep geological repositories (DGR) to store nuclear wastes. This study investigates the individual and combined effects of different chemical compositions of deep groundwaters (chemical factor) at potential repository sites in Canada (the Trenton and Guelph regions in Ontario), heat generated in DGRs (thermal factor), dry densities and mass ratios of bentonite and sand mixtures (physical factors) on the swelling behavior and ability of bentonite-based materials. In this study, swelling tests are conducted on B/S mixtures with different B/S mix ratios (20/80 to 70/30), compacted at different dry densities (ρd = 1.6–2 g/cm3), saturated with different types of water (distilled water and simulated deep groundwater of Trenton and Guelph) and exposed to different temperatures (20 °C–80 °C). Moreover, scanning electron microscopy (SEM) analyses, mercury intrusion porosimetry (MIP) tests and X-ray diffractometry (XRD) analyses are carried out to evaluate the morphological, microstructural and mineralogical characteristics of the B/S mixtures. The test results indicate that the swelling potential of the B/S mixtures is significantly affected by these physical and chemical factors as well as the combined effects of the chemical and thermal factors. A significant decrease in the swelling capacity is observed when the B/S materials are exposed to the aforementioned groundwaters. A large decrease in the swelling capacity is observed for higher bentonite content in the mixtures. Moreover, higher temperatures intensify the chemically-induced reduction of the swelling capacity of the B/S barrier materials. This decrease in the swelling capacity is caused by the chemical and/or microstructural changes of the materials. The results from this research will help engineers to design and build EBSs for DGRs with similar groundwater and thermal conditions.